Aqua{2-morpholino-N- 1-(2-pyridyl)ethylidene ethanamine-kappa N-3,N ',N ''}bis(thiocyanato-kappa N)cobalt(II) - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H.; Hisham, N.A.I. (International Union of Crystallography, 2011)
In the title complex, [Co(NCS)(2)(C13H19N3O)(H2O)], the Co-II ion is six-coordinated by the N,N',N ''-tridentate Schiff base, the N atoms of two thiocyanate ligands and one water molecule in a distorted octahedral geometry. Intramolecular C-H center dot center dot center dot N and C-H center dot center dot center dot O hydrogen bonds occur. In the crystal, intermolecular O-H center dot center dot center dot O, O-H center dot center dot center dot S, C-H center dot center dot center dot S and S center dot center dot center dot S [3.5546 (18) angstrom] interactions result in an infinite three-dimensional network.